If x + y = 0 , and y x 4 + 2 x 5 = 3 2 , solve for x.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x + y = 0 x = − y ⟹ y x 4 + 2 x 5 = 3 2 − x 5 + 2 x 5 = 3 2 x 5 = 3 2 x = 2
x+y=0 therefore y=-x
((-x) (x^4)) + 2x^5 =32
-x^5 + 2x^5 = 32
x^5=32
x=2
First separate the equation into yx^4+x^5+x^5+x^5, then factor out common terms x^4(x+y)+x^5. Now, we know that x+y=0, so we can negate the first part of the equation and we are left with x^5=32 therefore x=2.
x=2
Check your typo, u did write it (must be mistakenly) as x=32
Problem Loading...
Note Loading...
Set Loading...
We have x + y = 0
Hence, y = − x
Plugging into the equation given, we get :
( − x × x 4 ) + x 5 = 3 2
x 5 = 3 2
Hence, x = 2